Robust feedback stabilisation of homogeneous differential inclusions. Issue 1 (2nd January 2022) - Zimenko, K.; Polyakov, A.; Efimov, D.
ABSTRACT: The present paper is devoted to solution of the robust stabilisation problem for generalised homogeneous differential inclusions via dynamical feedback. The stability criterion is obtained. It is shown that asymptotically stable homogeneous differential inclusion is topologically equivalent to quadratically stable one via corresponding coordinate transformation. The results are supported with numerical examples of dynamical feedback design for an active suspension system.